A Review on the Successful Factors of Contributing to Graduate on Time (Got) Among PHD Holders - Maizura Abd Rashid, Intan; Ahmad Fauzi Wan Husain, Wan; Hanie Abu Samah, Irza; Harith Amlus, Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
This study is important so as to identify the successful factors for PhD students to graduate on time (GOT). However, the research will be carried out based on the PhD students in Malaysia, where it will cover all universities in Malaysia. This study used a data collection method that included administering questionnaires that were distributed to randomly selected students. A total number of 200 questionnaires were distributed according to different gender, age, race, and year of study to survey the successful factors for PhD students to graduate on time. The findings of this research will help the PhD students to understand further the factors and strategies for graduating on time during their PhD program. This study is particularly useful for PhD students to find out the behavior of young adults, especially in Perlis. The scope of this research covers the successful factors for PhD students to graduate on time. This study is also particularly useful for PhD students to have continuous improvement in their study. Besides that, PhD students can gain more ideas or suggestions on how to improve their study that can satisfy them and keep them committed to their study.